2016
DOI: 10.3368/le.92.3.389
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Natural Space on Nearby Property Prices: Accounting for Perceived Attractiveness

Abstract: This paper estimates the effect of attractive natural space on Dutch residential property prices. We operationalize attractive natural spaces by combining land use data with unique data on the perceived attractiveness of natural spaces. In our main results, the effect of attractive natural space on property prices falls from 16.0% for properties within 0.5 km, to 1.6% for properties up to 7 km away. Our findings advance existing hedonic studies by verifying that economic benefits of living near natural space e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 47 publications
1
38
0
1
Order By: Relevance
“…When HPM is used, it is necessary to assume that each individual is clearly aware of the circumstances surrounding the house and that the purchaser purchases the best housing desired [16].…”
Section: Methodsmentioning
confidence: 99%
“…When HPM is used, it is necessary to assume that each individual is clearly aware of the circumstances surrounding the house and that the purchaser purchases the best housing desired [16].…”
Section: Methodsmentioning
confidence: 99%
“…We use the range showing the highest estimate of these price gains. Research using the Hotspotsmonitor (Langers et al, 2013; Sijtsma et al, 2013a), a survey tool that measures landscape appreciation, suggests that housing value increments are much higher in appreciated natural areas than in green or nature areas which are merely classified as such in a land-use sense (Daams, 2016; Daams et al, 2016). Since the projected new housing in the assessed scenarios is likely to be built in such highly appreciated natural areas, our use of the highest price gain estimates seems to be justified.…”
Section: Methodsmentioning
confidence: 99%
“…There is evidence of a positive premium in housing prices at locations near open and green spaces that are perceived as beneficial and attractive (Daams, Sijtsma and Van der Vlist, 2016;Earnhart, 2006;Irwin and Bockstael, 2001) 1 . Analyses aimed to estimate the effects of open spaces on real estate values have found that in general proximity to these amenities has a positive impact (Conway, et al, 2010;Lutzenhiser and Netusil, 2001).…”
Section: Open Spaces and Property Valuesmentioning
confidence: 99%